THE CHANGE OF MANGROVE COVERAGE IN SEGARAANAKAN LAGOON OF CILACAP – CENTRAL JAVA - Bagus Oktori Sutrisno; Slamet Budi Prayitno (Research Center for Fisheries, 2013)
Mangrove ecosystem play san important role in coastal area. In several region mangrove coverage had decreased caused by various factors such as landuse change, erosion and sedimentation. Mangrove ecosystem in Segara Anakan Lagoon had decreased and damaged as well. The current work aimed to analyze the change of mangrove coverage in Segara Anakan Lagoon. A remote sensing analysis was conducted to deployeight years of satellite imagery data from 2002 to 2009. Analysis method included NDVI algorythm map processing which was associated with vegetation coverage in the area of interest. The results show that mangrove coverage in Segara Anakan Lagoon had decreased from 9,163.19 ha in 2002 to 8,433 ha in 2003, 7,764 ha in 2004, 7,252.72 ha in 2005 and 6,213.80 ha in 2006 respectvely. Further decrease occured in 2007 to 5,767.16 ha, 4,987 ha in 2008 and finally to 4,267.13 ha in 2009. Mangrove coverage is decreased approximately 677 ha each year. This decrease might be caused by several factors such as conversion of mangrove coverage to other utilization such as farming, housing and ponds, and high sedimentation rate from Citanduy river. These results suggest that management of mangrove area is needed to support coastal resources sustainability in Cilacap. Therefore, replantation andconservation of mangrove area could be applied for management purposes.